House price forecasts, forecaster herding, and the recent crisis - Christian Pierdzioch; Jan Christoph Rülke; Georg Stadtmann (International Journal of Financial Studies, 2013)
We used the Wall Street Journal survey data for the period 2006-2012 to analyze whether forecasts of house prices and housing starts provide evidence of (anti-)herding of forecasters. Forecasts are consistent with herding (anti-herding) of forecasters if forecasts are biased towards (away from) the consensus forecast. We found that anti-herding is prevalent among forecasters of house prices. We also report that, following the recent crisis, the prevalence of forecaster anti-herding seems to have changed over time.
Keywords: 330; forecasts; house prices; housing starts; herding